Physio-pathological risk factors from gallbladder affecting the conversion from laparoscopic cholecystectomy to open cholecystectomy - Yilmaz, Gokhan; Tanrikulu, Yusuf; Goksoy, Beslen (Annals of Medical Research, 2021)
Aim: Laparoscopic cholecystectomy is the first-line treatment method in the surgical treatment of gallbladder pathologies. Predicting conversion from laparoscopic to open cholecystectomy is still an important problem in the world. In our study, we aimed to investigate the gallbladder-derived physiopathological risk factors that affect the conversion from laparoscopic to open cholecystectomy.Materials and Methods: 370 patients who underwent cholecystectomy with the indications of symptomatic gallstone, acute cholecystitis, asymptomatic gallstones and gallbladder polyps were included in the study. Patients' demographic data such as age and sex, and pathological diagnoses, gallbladder wall thickness, and gallbladder volumes were obtained from pathology results. The effects of physiological parameters on conversion to open cholecystectomy were compared.Results: The most common indication for surgery is symptomatic gallstones (227 patients, 74.9%). The first preferred surgical technique is laparoscopic cholecystectomy with 86.5%. The conversion rate was 10.5% (n=39). The rate of conversion to open cholecystectomy was found to be high and a statistically significant difference was observed in patients with high gallbladder wall thickness and large sac volume (p0.001 for wall thickness, p=0.008 for gallbladder volume)Conclusions: We determined that the wall thickness and volume of the gallbladder had a significant effect on the conversion rate of laparoscopic cholecystectomy to open cholecystectomy. We believe that, patients who can be detected ultrasonographically prior to surgery with increased gallbladder wall thickness, and gallbladder volumes are more likely to conversion to open surgery and that patients should be informed in detail.
Keywords: Convert to open; cholecystectomy; gallstones; laparoscopy; risk factors